Pengaruh Inovasi Lingkungan Sebagai Pemoderasi Hubungan Antara Kinerja Lingkungan Terhadap Kinerja Keuangan - Khoirul Anam; Luluk Muhimatul Ifada (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2024)
The research objective is to analyse financial performance as influenced by environmental performance with environmental innovation as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2021 period. This research belongs to the quantitative category, utilising secondary data. Data sourced from annual reports and financial reports published by companies on the Indonesia Stock Exchange. This data collection uses purposive sampling technique with company selection criteria as many as 25 companies that are adjusted to the research objectives. The method used in this research is SmartPLS. The results showed that environmental performance can negatively and significantly affect environmental performance, as well as environmental innovation variables able to moderate the relationship between environmental performance and financial performance.